Development of a drainage and waste clearing machine - Ohijeagbon, Idehai O.; Ikuenayo, Vincent B.; Lasode, Olumuyiwa A.; Shaanika, Erasmus; Katte, Valentine Y.; Busari, Afis O. (Journal of Production Engineering, 2025)
Solid waste remains a critical environmental challenge globally, necessitating innovative solutions to alleviate its adverse impacts. This study aimed at enhancing solid waste management systems and mitigating the improper disposal of waste, particularly in drainage lines and the environment. The proposed solution involves the development of a waste and drainage clearing machine, designed to efficiently remove solid waste from drainage systems and roadside areas. Design analysis of the physical framework which included the buckling load analysis and structural integrity of the column, static load analysis of major components of the system, cantilever beam analysis of the looms, structural stability of the system was carried out. Results showed that the total weight of the machine is 384.75 kg and capable of clearing solid wastes from drainages at the rate of 300 kg per hour at 5 kg per operation, and can handle a maximum load of 10 kg in a single operation per minute. The portability of the machine also makes it suitable for narrow roads without undue obstruction to traffic. The innovation of this study is a potential source of employment and cost-effective service delivery with an overall benefit of guaranteeing a clean and healthy environment.